Building collaborative trust in construction procurement strategies - Challender, Jason; Farrell, Peter, 1955-; McDermott, Peter (Ohn Wiley & Sons, Inc., 2019)
"This book explores the concept of trust as a tool in improved construction procurement strategies, and provides important insight into the influence of trust on the success of construction projects and redevelopment programs. It is a practical guide that offers readers a solid outline and expert strategies for improving project outcomes through collaboration--ultimately proving that teamwork can really make the dream work."--Provided by publisher